The Learning English Assistance Program (LEAP) of Adamson University : a descriptive evaluation of its effectiveness - Yasa, Sinforosa Griño (Animo Repository, 1983)
This work is a descriptive evaluation of the effectiveness of Learning English Assistance Program (LEAP), a remedial activity at Adamson University on the semestral grades of freshmen students, analyzed in relation to certain variables such as age, sex, family income, type of high school graduated from and type of college students. The students were categorized as LEAP and non-LEAP.In order to concretize the investigation, an experimental design consisting of two (2) groups (LEAP I) and a control group (non-LEAP) was constructed. Antecedent data on the 5 variables and attitudes of students on methods of instruction, faculty, and instructional materials used were gathered. The descriptive method of investigation gathered information on the English Department and the LEAP I program. To carry out the research design, the College Scholastic Aptitude Test (CSAT) and the semestral grades for the first semester of SY 1982-83 in English were the measuring instruments used. The attitudes of students about the LEAP were measured by the Students' Perception Inventory constructed for this purpose. A questionnaire on Methodology based on William Mackay's Meaning of Method was used to measure the methods of instruction. A sample of 100 students was taken from those who took the 1982-83 CSAT and who enrolled in the LEAP I program. A random sample from the non-LEAP students was taken from every 10th student within the 52 classes in English I. Statistical tools were the one factor, one co-variate analysis of co-variance, ANOVA, the t-test, the Pearson product moment correlation, and the test for independent proportion. The findings presented, analyzed and interpreted based on guidelines to the inferential techniques used led to the conclusion that the performance of LEAP students did not differ significantly from the non-LEAP students in almost all areas of the investigation. However, some significant differences were found among non-engineering students in the LEAP program who achieved significantly better than the non-LEAP eng